(untitled) (Research, Society and Development, 2020)
Objective: To carry out a morphoanatomical and phytochemical study of samples from the Jatropha multifida plant by analyzing the macro and microscopic characteristics, as well as performing tests to detect classes of metabolites. Methodology: The morphoanatomical analysis of the plant was carried out through sections of the adaxial and abaxial sides of the leaf blade and cross sections of the middle third including the central vein of the leaves of the plant, freehand, and, later, stained with methylene blue and fuchsin and observed under an optical microscope. In the phytochemical study, hydroalcoholic extract of the leaves of Jatropha multifida was used in tests to detect phenols, tannins, flavonoids, coumarins, steroids, triterpenes, saponins, alkaloids and resins. Results: Jatropha multifida leaf was concolor, acuminated, palmatipartite, hypoestomatic with anomocytic stomata, cell epidermis with curved wall, dorsiventral mesophyll, collateral vascular bundle and druses. Regarding phytochemical tests, the presence of tannins, coumarins, steroids and triterpenes, saponins and alkaloids was detected. Conclusion: Through the observations and tests carried out it was possible to characterize Jatropha multifida, which can help in the differentiation of this species from other similar, as well as in the standardization of this vegetable raw material.